Reading as a language skill and methods of vocabulary development in Czech as a foreign language - Stary Koranova, Ilona (Bohemica Olomucensia, 2019)
The article deals with some general issues of reading as a language skill and its role in acquiring Czech as a foreign language. While doing so, it focuses on following questions: Is reading a passively receptive skill only?, Why is reading important in the learning/teaching process?, What is the relevance of grammar and lexicon in this process? What are the inference strategies in acquiring new lexical items?, and finally, What are the phases in working with the text from the learners' Czech vocabulary development point of view?
Keywords: Reading in Czech; Czech as a foreign language; vocabulary development; inferential strategies; chunks (PSS)